Possible Facilitative Effects of Repeated Anodal Transcranial Direct Current Stimulation on Functional Outcome 1 Month Later in Schizophrenia: An Open Trial - Narita, Zui; Inagawa, Takuma; Sueyoshi, Kazuki; Lin, Crystal; Sumiyoshi, Tomiki (Frontiers in Psychiatry, 2017)
Recent research on neuromodulation techniques, such as transcranial direct current stimulation (tDCS), for the treatment of schizophrenia has mainly focused on psychotic symptoms. We aimed to determine whether repetitive tDCS is efficacious in improving determinants of outcome, such as cognitive function, daily living skills, and depressive mood in patients with schizophrenia. Twenty-eight patients underwent tDCS (2 mA × 20 min) two times per day for 5 consecutive days. The anodal electrode was placed over the left dorsolateral prefrontal cortex while the cathodal electrode was placed over the right supraorbital region. One month after the last stimulation, there was a significant improvement on cognitive function, measured by the brief assessment of cognition in schizophrenia (d = 0.49). Significant effects were also shown on daily living skills (functional capacity), measured by the UCSD performance-based skills assessment-brief (d = 0.70). Depressive symptoms, measured by the Calgary depression rating scale, as well as psychotic symptoms measured by on the positive and negative syndrome scale positive and general psychopathology subscales also responded to the treatment (d = 0.38, d = 0.48, and d = 0.50, respectively). This is the first study to suggest that tDCS with the anodal electrode on the left prefrontal cortex improves functional capacity and depressive symptoms in patients with schizophrenia. These results may add to the concept that tDCS provides a strategy to enhance functional outcomes in patients with schizophrenia. Trial Registration https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr_view.cgi?recptno=R000018556, UMIN000015953.